Reopening the Langelier—Mignault Debate on Unauthorized Transactions Involving a Minor's Property - Krane, Joshua; Lubetsky, Michael (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2009)
Under section 213 C.C.Q., immovables, enterprises, and important pieces of family property belonging to a minor can only be sold in cases of necessity, and only then with prior authorization from the court or the tutorship council. What is the legal status, therefore, of a contract of sale of a minor's property made by his tutor in violation of this provision? This question inspired a vigorous debate in both France and Quebec throughout the nineteenth century. Mignault "settled'' this debate in 1896 by declaring such a contract to be tainted with relative nullity. Now, over a century later, the law's attitude toward the protection of minors has changed significantly, which makes it appropriate to revisit Mignault's thesis. This paper argues that the sanction of relative nullity is inconsistent with both the text and underlying policy objectives of the section, and that an alternative approach must be adopted.